Foam rolling acute effects on myofascial tissue stiffness and muscle strength: a systematic review and meta-analysis - Glänzel, M. H.; Rodrigues, D. R.; Petter, G. N.; Pozzobon, D. Vaz, M. A.; Geremia, J. M. (The Journal of Strength and Conditioning Research, 2023)
Foam rolling (FR) is widely used in rehabilitation and physical training. However, the effects of FR on myofascial tissue stiffness and muscle strength remain unclear. This study aimed to perform a systematic review with meta-analysis of trials that tested the FR acute effects during warm-up on the myofascial tissue stiffness and muscle strength in healthy adults or athletes. This systematic review (CRD42021227048) was performed according to Cochrane's recommendations, with searches performed in PubMed, Web of Science, Embase, and PEDro databases. Syntheses of included studies' data were performed, and the PEDro scale was used to assess the methodological quality of the studies. Certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluations approach. Twenty included studies assessed trunk and thigh fascial tissue stiffness, and thigh and calf muscle stiffness, whereas muscle strength was assessed in the knee extensors and flexors, and plantar flexors muscles. Qualitative analysis showed decreases in fascial (n = 2) and muscle (n = 5) stiffness after FR. However, the meta-analysis showed no effects of FR on myofascial tissue stiffness. Both qualitative and quantitative analyses showed no effects of FR on isometric muscle strength, eccentric torque, and rate of force development. However, the knee extensor concentric torque increased after FR. Foam rolling increases the knee extensor concentric torque, but it does not acutely change the myofascial tissue stiffness and isometric muscle strength. However, evidence of these studies provides low certainty to state that FR does not change these parameters. Therefore, high methodological quality studies should be performed to better ascertain the effects of FR on the myofascial tissue stiffness and muscle strength.